Characterization of a local germplasm of sulla (Hedysarum coronarium) in the north of Morocco - Noutfia A.; Mrabet R.; El Mourabit N.; Ayadi M.; El Othmani S. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
In the west-northern region of Morocco, the sulla (Hedysarum spp) an endemic forage plant is subject to severe genetic erosion that needs a special attention to preserve and to valorise this patrimony. In this context this study was carried out to collect and characterize local germplasm. Thirty ecotypes were collected and compared with Italian and Spanish varieties. Agronomic assessment showed that 80% of collected ecotypes were creeping types and 20% were upright ecotypes. They were conducted as monocropping and gave yield exceeding 10 tons per hectare of dry matter. Plant chemical analysis indicated that the local germplasm showed a higher protein content than Italian and Spanish varieties: 25.9, 23.1, and 14.1%, res - pec tively. For the cellulose content, no significant differences were found among ecotypes (20% of DM). As conclusion, since local germplasm presented better productivity indexes it is evident to conduct a breeding program for development of this crop as strategic feed resource for the region.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)